Pengaruh Ukuran Perusahaan Dan Struktur Kepemilikan Terhadap Nilai Perusahaan Melalui Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Manufaktur (Sub-Sektor Makanan Dan Minuman) Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2024 - Sania Audy Nabila; Elfiswandi .; Putri Intan Permata Sari (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to examine how company size and ownership structure affect company value through profitability as an intervening variable in manufacturing companies (food and beverage sub-sector) listed on the Indonesia Stock Exchange for the period 2020-2024. The research method used in determining the sample was purposive sampling. Based on several predetermined criteria, this study used 28 manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2020-2024. The test method used SPSS data processing. The results of this study indicate that in the t-test, company size and ownership structure affect profitability. Company size affects company value, while ownership structure does not affect company value. Profitability affects company value. The path analysis test shows that company size does not affect company value through profitability as an intervening variable. Ownership structure does not affect company value through profitability as an intervening variable.